Caries experience in preschool children over a 10-year period - Garbin, Clea Adas Saliba [UNESP]; Saliba, Tânia Adas [UNESP]; Teruel, Gabriela Peres [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Artênio José ísper [UNESP] (My University, 2019)
Purpose: To analyse the caries experience in preschool children at two moments 10 years apart. Materials and Methods: Two cross-sectional epidemiological studies, the first in 2006 (n = 275) and the second in 2016 (n = 258), were carried out with samples composed of children from 3 to 6 years of age. All children were enrolled in the municipal schools of basic education of a municipality in northwest São Paulo state, and they attended an annual and continuous oral health education programme. Caries experience was calculated for deciduous and permanent teeth using the dmft and DMFT indices, according to the World Health Organization (WHO). Statistical analysis was performed using Epi info 7.1 and Bioestat 5.0 software. Results: In 2006, the mean dmft index was 1.88, with 7.59% of teeth having caries experience. In 2016, the mean dmft index was 0.99, with 5.15% of teeth showing caries experience. In contrast, in 2006, the mean DMFT index was 0.08 (n = 509), with 4.1% of teeth with caries experience; in 2016, the mean DMFT index was 0.06 (n = 381) and 3.6% of teeth showed caries experience. The proportions of teeth with caries experience differed statistically significantly (p = 0.435). In the last study, 78.2% of the children were caries free, below the WHO target for 2020. The Significant Caries Index (SiC Index) was 0.2. Conclusion: A decline of caries experience in the deciduous dentition was found in the study population.
Keywords: Epidemiological surveys; Oral health; Preschoolers